Effects of GDNF on neurovascular structures during recovery process after cerebral ischemia - Beker, Merve; Beker, Mustafa Çağlar; Çağlayan, Ahmet Burak; Köse Torun, Gamze; Kılıç, Ertuğrul (Wiley, 2019)
[Abstract Not Available]
Keywords: GDNF; Neurovascular; Structures; Cerebral Ischemia